Three Decades of Post-Secondary Strategy in Manitoba - Smith, Dan (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2025)
This article explores the impact of post-secondary system reviews in Manitoba in the three decades since 1993. During this timeframe, eight such reviews were undertaken, expressing key objectives for the system that included better alignment with provincial economic priorities, stronger system coordination, and increased accessibility. Despite the consistent appearance of these objectives across all reviews, governments did not always pursue them with sufficient energy to bring them to fruition, shaping how these reviews affected the approach to post-secondary policy in Manitoba.